Impact of Robotic Surgery on Residency Training for Herniorrhaphy and Cholecystectomy. Issue 10 (25th October 2020) - Kadakia, Nikita; Malek, Kirollos; Lee, Sarah K.; Lee, Eun J.; Burruss, Sigrid; Srikureja, Daniel; Mukherjee, Kaushik; Lum, Sharon S.
Robotic surgery has increased for common general surgery procedures. This study evaluates how robotic use affects the case distributions of herniorrhaphy and cholecystectomy for general surgery residents according to postgraduate year (PGY). We reviewed Accreditation Council for Graduate Medical Education (ACGME) biliary or hernia cases logged by surgical residents in the academic year 2017-2018. Operative reports were reviewed to compare approaches (robotic, laparoscopic, and open) by resident role and PGY level. Open cholecystectomies were excluded. Overall, 470 hernia and 657 cholecystectomy cases were logged. Hernia repairs were performed robotically in 15.9%, laparoscopically in 9.5%, and open in 74.7%. Cholecystectomies were performed robotically in 16.4% and laparoscopically in 83.6%. Residents were teaching assistants in 1.8% of hernia repairs and 1.5% of cholecystectomies. Distribution of cases by technique and PGY level was significantly different for both procedures, with chief residents performing the majority of robotic cholecystectomies (52.6%, P < .0001) and hernia repairs (59.7%, P < .0001). Migration of robotic cases to senior resident level and low percentage of teaching assistant roles held by residents suggest exposure to common operations may be delayed during general surgery residency training. Introduction of new technology in surgical training should be carefully reviewed and may benefit from a structured curriculum.